2021
DOI: 10.1039/d0cs01261k
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RNA with small molecules: from fundamental principles towards the clinic

Abstract: This tutorial review describes the fundamental principles and recent advances in developing small molecule-based therapeutics for disease-associated RNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 55 publications
1
129
0
Order By: Relevance
“…It's reported that RNA-targeted fluorescent probes commonly consist of aromatic rings, nitrogen heterocyclic rings and amine groups. 34,35 Phenylenediamines are commonly used precursors for preparing CDs to provide heterocyclic compounds and polymers. According to previous reports, CDs prepared by m-PD have potential in targeting nucleolar RNA.…”
Section: Fabrication and Characterization Of Rna-cdsmentioning
confidence: 99%
“…It's reported that RNA-targeted fluorescent probes commonly consist of aromatic rings, nitrogen heterocyclic rings and amine groups. 34,35 Phenylenediamines are commonly used precursors for preparing CDs to provide heterocyclic compounds and polymers. According to previous reports, CDs prepared by m-PD have potential in targeting nucleolar RNA.…”
Section: Fabrication and Characterization Of Rna-cdsmentioning
confidence: 99%
“…RNA targets that expand druggable genome, including those linked to ‘undruggable’ protein targets or non-coding microRNAs, are of particular interest ( 5 ). However, RNA drug development is dotted with numerous obstacles ( 6 ), among others, related to the low chemical diversity and the dynamic nature of RNA structures. Similar to proteins, RNA molecules are highly structured to form binding sites, through which small molecules can modulate them ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 The rapidly increasing amount of publications on RNA-targeting molecules points out the emerging importance of this interdisciplinary research area. [14][15][16][17][18][19] Similar to DNA and proteins, RNA possesses a range of important features as a drug target. Like DNA, the chemical building units of RNA are fewer and less complex in comparison to those of proteins.…”
Section: Introductionmentioning
confidence: 99%